PAM50 Molecular Intrinsic Subtypes in the Nurses’ Health Study Cohorts - Kensler, Kevin H. (Cancer Epidemiol Biomarkers Prev, 2018)
BACKGROUND: Modified median and subgroup-specific gene centering are two essential pre-processing methods to assign breast cancer molecular subtypes by PAM50. We evaluated the PAM50 subtypes derived from both methods in a subset of Nurses’ Health Study (NHS) and NHSII participants; correlated tumor subtypes by PAM50 with immunohistochemistry (IHC) surrogates; and characterized the PAM50 subtype distribution, proliferation scores and risk of relapse with proliferation and tumor size weighted (ROR-PT) scores in the NHS/NHSII. METHODS: PAM50 subtypes, proliferation scores and ROR-PT scores were calculated for 882 invasive breast tumors and 695 histologically normal tumor-adjacent tissues. Cox proportional hazard models evaluated the relationship between PAM50 subtypes or ROR-PT scores/groups with recurrence free survival (RFS) or distant RFS. RESULTS: PAM50 subtypes were highly comparable between the two methods. The agreement between tumor subtypes by PAM50 and IHC surrogates improved to fair when Luminal subtypes were grouped together. Using the modified median method, our study consisted of 46% Luminal A, 18% Luminal B, 14% HER2-enriched, 15% Basal-like and 8% Normal-like subtypes; 53% of tumor-adjacent tissues were Normal-like. Women with the Basal-like subtype had a higher rate of relapse within five years. HER2-enriched subtypes had poorer outcomes prior to 1999. CONCLUSION: Either pre-processing method may be utilized to derive PAM50 subtypes for future studies. The majority of NHS/NHSII tumor and tumor-adjacent tissues were classified as Luminal A and Normal-like, respectively. IMPACT: Pre-processing methods are important for the accurate assignment of PAM50 subtypes. These data provide evidence that either pre-processing method can be used in epidemiological studies.